Brand expansion for an original IP through collaboration: a case study of Disney’s animated film Wish - Lee, Jun; Kim, Kenneth Chi Ho (Frontiers in Communication, 2026)
IntroductionIn this study, we explore how collaboration with K-pop idols influences brand expansion (operationalized as increases in awareness, attitudes, and behavioral intentions) for original intellectual property, focusing on Disney’s animated film Wish (2023). As a standalone production with no ties to previous franchises or source material, Wish was created to commemorate Disney’s 100th anniversary. Without an established fanbase, the film faced structural challenges in attracting early interest. The similarly positioned Strange World (2022), which lacked significant collaborations or innovative marketing, underperformed at the box office, highlighting the difficulty of promoting unfamiliar titles.MethodsTo address this challenge, Wish adopted a K-pop-driven strategy by featuring An Yujin of the girl group IVE in the official music video for the original song “This Wish.” This collaboration increased both visibility and positive perceptions of the film. By combining Disney’s global brand recognition with the cultural influence of K-pop, the campaign helped overcome barriers related to brand unfamiliarity. A survey of viewers of the “This Wish” music video assessed their perceptions of the collaboration, levels of fan activity, and extent of brand expansion. Structural equation modeling was used to examine whether fan activity mediated the relationship between collaboration and brand expansion.ResultsThe results showed that K-pop collaboration positively influenced brand expansion both directly and indirectly through fan engagement. Activities such as media consumption, content creation, and social media sharing significantly contributed to audience awareness and acceptance of the original intellectual property film.DiscussionThese findings suggest that cross-industry collaborations between K-pop and film can promote fan-driven consumption and serve as effective branding strategies for original intellectual property in global markets. From a transnational cinema perspective, the partnership between K-pop idols and global media illustrates a hybrid cultural model that enhances cross-border recognition and offers strategic insights for future content marketing.